1987
DOI: 10.1111/j.1558-5646.1987.tb05795.x
|View full text |Cite
|
Sign up to set email alerts
|

GEOGRAPHIC VARIATION WITHIN AN ISLAND: UNIVARIATE AND MULTIVARIATE CONTOURING OF SCALATION, SIZE, AND SHAPE OF THE LIZARDGALLOTIA GALLOTI

Abstract: Abstract.-Microgeographic variation of the vegetarian lizard Gal/otia gal/oti within the island of Tenerife is described using univariate analysis, correlation, multiple group principal component analysis, canonical analysis, transects, and contours. The size varies locally in a mosaic pattern while head shape shows a WNW-ESE dine in the south. The scalation (scale and femoral pore counts) has two facets to its geographic variation, both of which are incongruent with the primary variation in the size and shape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The rejected allopatry hypotheses (1)(2)(3)(4) are also unlikely on other grounds. This hypothesis (6) has the highest and most significant partial correlation with the generalized pattern and all individual characters, except for the number of blue blotches.…”
Section: Research Articlesmentioning
confidence: 99%
“…The rejected allopatry hypotheses (1)(2)(3)(4) are also unlikely on other grounds. This hypothesis (6) has the highest and most significant partial correlation with the generalized pattern and all individual characters, except for the number of blue blotches.…”
Section: Research Articlesmentioning
confidence: 99%
“…The latter aspect is important because due to sexual differences in reproductive and ecological roles, some factors can affect one sex more than the other. As a result, geographic patterns in body size may differ markedly between males and females (Herczeg, Gonda, & Merilä, 2010;Pearson, Shine, & Williams, 2002;Roitberg et al, 2015;Saino & De Bernardi, 1994;Thorpe & Baez, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicated that variation in scale numbers is often correlated with climate; hotter and drier conditions may favor either fewer but larger scales [140], [141] or a greater number of smaller scales [142], [143]. Sanders et al [144] studied variation in scalation in nocturnal and arboreal Trimeresurus snakes, which also show an increase in scale numbers in hotter and drier climates.…”
Section: Resultsmentioning
confidence: 99%